Between Proverb and Poem in the Sephardic Tradition - Alexander, Tamar (MiKAN, 2012)
The article's aim is to characterize several of the inter-genre links between the proverb form and the traditional poems of Sephardic Jewry. These connections are examined for the three main genres of Sephardic traditional poetry, the romanca, the copla, and the canción. The article proposes a model for categorizing these links according to four different phenomena: (a) a proverb interpolated into a poem; (b) a proverb adapted for inclusion in a poem; (c) a line from a poem becoming a proverb; (d) a proverb co-opted by a poem. In each case, the poem and the proverb gain from one another. Poems serve as additional sources for the creation of new proverbs, provide proverbs with new contexts that imbue them with further meaning, and serve as another channel for the transmission of proverbs within the community. Proverbs, in turn, provide poems (especially new ones) with collective authority and tradition, help introduce them to audiences already familiar with the proverbs, and encourage audiences to view them as expressions of truth.